A DESCRIPTIVE STUDY ON RISK FACTORS AND COMORBID CONDITIONS OF CEREBRAL PALSY CASES ATTENDING DEIC, S.V.P.PG INSTITUTE (SISHU BHAWAN), CUTTACK - SANGHAMITRA SANDHIBIGRAHA; RAMA CHANDRA GIRI; NIVEDITA KARMEE; VIVEKANANDA ACHARYA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The objectives of the study were: (1) To study the sociodemographic profile of cerebral palsy (CP) cases attending the District Early Intervention Center (DEIC) at Sishu Bhawan. (2) To study the risk factors of CP. (3) To study the associated comorbid conditions of CP. Methods: It is a hospital-based study conducted at DEIC, Sishu Bhawan, Cuttack, from July 2016 to June 2017. All cases (150) of CP children in the age group of 6 months–14 years attending DEIC during the study period were taken as study subjects. The mothers/caregivers of the children were interviewed, and the data thus collected were analyzed by the Statistical Package for the Social Sciences version 17. Results: The mean age of the study subjects was 2.87 years±2.48 standard deviation. The male–female ratio was 2.4. The risk factors associated with CP were PIH, antepartum hemorrhage, low birth weight, hyperbilirubinemia, seizures, birth asphyxia, etc. The common comorbid conditions are malnutrition, mental retardation, seizure, hearing and vision impairment, speech difficulty, and behavioral problems. Conclusion: Prevention of prenatal, perinatal, and postnatal risk factors of CP and better management of high-risk cases will reduce the occurrence of CP.